Thallium exposure at low concentration leads to early damage on multiple organs in children: A case study followed-up for four years. (March 2020) - Duan, Weixia; Wang, Yongyi; Li, Zhiqiang; Fu, Guanyan; Mao, Longchun; Song, Yunbo; Qu, Yaping; Ye, Lvsu; Zhou, Qu; Yang, Fucheng; Hu, Zhide; Xu, Shangcheng
Abstract: Thallium (TI) is one of the most toxic heavy metals and priority pollutant metals. The emerging TI environmental pollution worldwide has posed a great threat to human health. However, based on the World Health Organization (WHO), the risk and severity of adverse health effects of TI in the range of 5–500 μg/L are uncertain. Moreover, evidence regarding the adverse impacts of TI on children's health is still insufficient. Herein, we aim to investigate the early adverse effects of TI on children's health and provide references for the WHO to establish stricter safety limits of TI. From 2015 to 2019, urinary TI and many clinical laboratory parameters related to blood routine, hepatic, renal, myocardial, coagulation function and serum electrolyte were measured in six children aged 1–9 years. The urinary TI concentration ranged from 13.4 μg/L to 60.1 μg/L with a mean of 36.1 μg/L and a median of 34.8 μg/L in six children in 2015. Although only four children felt a little poor appetite, several laboratory abnormalities indicated early damage in liver, renal, and myocardial functions in all children in 2015. After treatment and following up for four years, although the children's TI concentration decreased below 5 μg/L, their liver and renal functions did not completely recover, and their myocardial function worsened. Results indicated that impaired liver, renal, and myocardial functions were closely associated with elevated urinary TI concentration in children. Considering the increasing use of TI in high-technology industries and emerging TI environmental-contamination zones worldwide, establishing stricter safety limits of TI and paying more attention to the adverse health effects of TI on children are urgently required. Summary: We found that a relatively low concentration of thallium (13.4 μg/L to 60.1 μg/L) impaired liver, renal, and myocardial function in six children. After treatment and following up these children for four years, although their urinary TI concentration decreased below 5 μg/L, their liver and renal functions did not completely recover, and their myocardial function worsened. Graphical abstract: Image 1 Highlights: The urinary TI and several clinical laboratory parameters were monitored in six children for 5 years. Relatively low concentration of TI results in early damage in multiple organs at sub-clinical level. Theadverse effects of TI on the myocardial function may get worse over time. The study emphasizes the early adverse effects of TI on children health. The study provides references for the WHO to establish stricter safety limits of TI.